ANALISIS INSTAGRAM @THEFARMPANCAWATI DALAM MENINGKATKAN DAYA TARIK PARIWISATA - Putri, Aura Fidya; Rusfien, Ismail Taufik (Media Bahasa, Sastra, dan Budaya Wahana, 2025)
This study aims to analyze the use of the Instagram account@thefarmpancawati as a public relations medium in enhancing tourism attraction. The background of this research focuses on the issue of declining visitor numbers. Based on this, the Instagram account @thefarmpancawati is utilized to increase visitor interest by actively engaging and sharing various appealing content. This study uses a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. The results indicate that the @thefarmpancawati account is effectively used as a medium for two-way interaction, information dissemination through content such as high-quality photo and video posts, persuasive captions, as well as Instagram Stories and Reels to attract potential visitors. However, the effectiveness of the information delivery is still influenced by the consistency of posts and competition with other tourist attractions in the surrounding area. This study concludes that Instagram plays an important role in increasing visitor interest through engaging content and active interaction.Keywords: Instagram, public relations, tourism,